1996
DOI: 10.1038/bjc.1996.307
|View full text |Cite
|
Sign up to set email alerts
|

Deficient DNA repair capacity, a predisposing factor in breast cancer

Abstract: Summary Women with breast cancer and a family history of breast cancer and some with sporadic breast cancer are deficient in the repair of radiation-induced DNA damage compared with normal donors with no family history of breast cancer. DNA repair was measured indirectly by quantifying chromatid breaks in phytohaemagglutinin (PHA)-stimulated blood lymphocytes after either X-irradiation or UV-C exposure, with or without post treatment with the DNA repair inhibitor, l-fl-D-arabinofuranosylcytosine (ara-C). We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
100
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(107 citation statements)
references
References 32 publications
6
100
1
Order By: Relevance
“…Using an assay for detecting X-ray induced chromosome damage in lymphocytes in the G2 phase of the cell cycle we found that approximately 40% (21 out of 50) of an unselected series of breast cancer cases showed elevated chromosomal radiosensitivity compared with normal, healthy controls (Scott et al, 1994). This observation has recently been confirmed by Parshad et al (1996) who found that 6 out of 12 cases with no family history of breast cancer and six out of seven cases with a family history were sensitive. Although the family history cases were not screened for mutations in the BRCAJ and BRCA2 genes, which confer a very high risk in about 5% of breast cancer cases (Ford and Easton, 1996;Goldgar et al, 1996), it is relevant to note that these genes appear to have a role in repair of DNA double-strand breaks (Kinsier and Vogelstein, 1997), the lesions directly involved in chromosome aberration formation (Natarajan et al, 1990).…”
mentioning
confidence: 66%
“…Using an assay for detecting X-ray induced chromosome damage in lymphocytes in the G2 phase of the cell cycle we found that approximately 40% (21 out of 50) of an unselected series of breast cancer cases showed elevated chromosomal radiosensitivity compared with normal, healthy controls (Scott et al, 1994). This observation has recently been confirmed by Parshad et al (1996) who found that 6 out of 12 cases with no family history of breast cancer and six out of seven cases with a family history were sensitive. Although the family history cases were not screened for mutations in the BRCAJ and BRCA2 genes, which confer a very high risk in about 5% of breast cancer cases (Ford and Easton, 1996;Goldgar et al, 1996), it is relevant to note that these genes appear to have a role in repair of DNA double-strand breaks (Kinsier and Vogelstein, 1997), the lesions directly involved in chromosome aberration formation (Natarajan et al, 1990).…”
mentioning
confidence: 66%
“…These chromosome breakage syndromes are characterised by various defects in DNA repair, predisposition to different forms of malignancy and increased radiosensitivity (for a review, see Carney 1999). Apart from these rare syndromes, the deficient DNA repair capacity has been proposed to be a predisposing factor in familial BC and in some sporadic BC cases (Parshad et al, 1996). Genomic instability has also been described for various hereditary cancers including hereditary BC (Rothfuß et al, 2000;Baeyens et al, 2002).…”
mentioning
confidence: 99%
“…Some of these studies have revealed reduced DNA repair capacity in peripheral blood mononuclear cells (PBMCs, exposed in vitro to ionising radiation (IR) or UV) from BC patients, as evaluated by the chromosome aberration assay (Rigaud et al, 1990;Helzlsouer et al, 1995;Parshad et al, 1996) as well as by the MN test (Scott et al, 1998Baeyens et al, 2002). Furthermore, a series of studies have found elevated G2 chromosomal radiosensitivity in the blood cells from BC patients (Baria et al, 2001;Riches et al, 2001;Baeyens et al, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This has been shown in cancer-prone syndromes (reviewed in Scott et al 1998). breast cancer patients (Scott et al 1994: Parshad et al 1996 and healthy control subjects (Knight et al 1993). In contrast.…”
mentioning
confidence: 99%